Analisis Strategi Rantai Nilai (Value Chain) Untuk Keunggulan Kompetitif Melalui Pendekatan Manajemen Biaya - Rahmah, Novia Hidayatul; Animah; Zuhrotul Isnaini (Fakultas Ekonomi dan Bisnis Unram, 2025)
This study aims to determine the effect of value chain and cost management on competitive advantage at Rosa Catering. To support this research, of course, accurate and precise data is needed, so that the discussion and data are in accordance with what is in the field. The place used as the object of research is Rosa Catering which is located on Jalan Palapa II Karang Tapen, Cakranegara, West Nusa Tenggara. This research is a quantitative study with a descriptive approach. The results of the study indicate that the application of the value chain has a positive effect on the company's competitive advantage. Rosa Catering only relies on one place of business as the object of research and may not be generalized to the entire population of catering businesses due to differences in characteristics and conditions between businesses. The results of further research are expected to expand more diverse samples in various types of catering businesses, both small, medium, and large scale, as well as in various geographic locations.